The scale-invariant properties of the citation-based performance of internationally co-authored articles - Ronda-Pupo, Guillermo Armando (Malaysian Journal of Library and Information Science, 2018)
The aim of this paper is to determine the scale-invariant properties of the citation-based performance of internationally co-authored articles on Management Information Systems (MIS). A total of 20, 485 articles which received a total of 432,386 citations were analyzed. Collaborative articles accounted for 83 percent of the papers. Citation-based performance and international collaborative papers exhibited a power-law correlation with a scaling exponent of 1.28 ± 0.05. Citations to MIS articles increased 21.28 or 2.42 with a doubling of the number of internationally collaborative papers. The scaling exponent for the power-law correlation for domestic collaborative papers was 1.22 ± 0.04 indicating that citations grew by 21.22or 2.32 times when the number of domestic papers doubled. MIS articles published through international collaboration show a stronger Matthew Effect than those published through domestic collaboration. International collaborative papers were further analyzed by global regions. The papers that were internationally collaborative with authors being from different global regions have a scaling exponent for the power-law correlation with citation-based performance of 1.25 ± 0.06. This exponent shows that citations grew 21.26±0.06 or 2.37 times when the number of these inter-regional papers doubled. Those papers that were internationally collaborative with the authors being from the same global region (intra-regional) have a scaling exponent for the power-law correlation with citation-based performance of 1.56 ± 0.14. This performance demonstrates that citations grew 21.56±0.14 or 2.94 times when the number of intra-regional papers doubled. This indicates that the Matthew Effect is stronger for intra-regional collaborative papers than for inter-regional ones.